Optimization of Three-Level Cervical Hybrid Surgery to Prevent Adjacent Segment Disease: A Finite Element Study - Wong, Chia-En; Hu, Hsuan-Teh; Hsieh, Meng-Pu; Huang, Kuo-Yuan (Frontiers in Bioengineering and Biotechnology, 2020)
Hybrid surgery (HS) allows surgeons to tailor fusion and arthroplasty in the treatment of multiple-level cervical disc degeneration. However, the decision making of selecting either ACDF or ADR for each level in three-level HS remains controversial and has not been fully investigated. This study was aimed to optimize three-level cervical hybrid constructs by systematically investigating their biomechanical properties and their effect on adjacent levels. A finite element model of cervical spine (C2-C7) was developed, and eight C3-C6 surgical models including six HS were constructed. The range of motion(ROM) in flexion, extension, lateral bending, and axial rotation under 2.0 Nm moments with 30 N follower load were simulated. The von Mises stress, strain energy at the adjacent intervertebral disc(IVD) and force at the adjacent facet were calculated. The ROM of the hybrid constructs and adjacent levels was close to that of the intact spine. HS with arthroplasty performed at C5-6 had better performance in terms of ROM reduction at the inferior adjacent level (C6-7). Moreover, C-D-D and 3ADR had best performance in reducing the von Mises stress and strain energy at C6-7. All HS reduced the facet burden at both C2-3 and C6-7 levels. However, the major drawback of HS revealed here is that the effect of C6-7 protection is at the cost of increased C2-3 IVD burden. In conclusion, we recommend C-D-D and 3ADR for patient with C3-C6 disc degeneration without predisposing C2-3 condition. C-C-D could be a good alternative with a lower medical cost. This analysis guides the decision making in three-level cervical hybrid surgery before future cadaver studies or human clinical trials.